A METHODOLOGY FOR PRE-HARVEST PREDICTION OF MEAN POTATO YIELD AT REGIONAL SCALE USING INFOCROP-POTATO MODEL - Govindakrishnan, P M; Singh, J. P; Lal, S S; Panigrahy, Sushma (Potato Journal, 2013)
Using a simulation model INFOCROP-POTATO, the mean tuber yield for a region was estimated by the equation Y = P x 1/T x (1-R) where, Y is mean tuber yield forecasted; P is potential or maximum possible tuber yield of potato; T is factor for the fraction of P realised due to technological level; R is percent reduction in yield expected due to any one or combination of factors beyond control during the crop growth period. The model was validated for two major states of Punjab and West Bengal from the observed mean tuber yield data of 18 and 8 years, respectively. The performance of the prediction method was satisfactory. The root mean square error (RMSE) of the predicted tuber yield expressed as percentage of the observed mean was only 10 and 8% for the states of Punjab and West Bengal, respectively. The coefficient of residual mass (CRM) indicated only slight errors of over or under estimation. The percent deviations in predicted tuber yield from the actual observed tuber yield was less than 10% in most of the years both in Punjab and West Bengal.